Optimisation of a Molecular Dynamics Simulation of Chromosome Condensation - Law, Timothy R.; Hancox, Jonny; Cheng, Tammy M. K.; Chaleil, Raphaël A. G.; Wright, Steven A.; Bates, Paul A.; Jarvis, Stephen A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2016: Anais do XXVIII International Symposium on Computer Architecture and High Performance Computing, 2016)
We present optimisations applied to a bespoke bio-physical molecular dynamics simulation designed to investigate chromosome condensation. Our primary focus is on domain-specific algorithmic improvements to determining short-range interaction forces between particles, as certain qualities of the simulation render traditional methods less effective. We implement tuned versions of the code for both traditional CPU architectures and the modern many-core architecture found in the Intel Xeon Phi coprocessor and compare their effectiveness. We achieve speed-ups starting at a factor of 10 over the original code, facilitating more detailed and larger-scale experiments.